2020
DOI: 10.23736/s0022-4707.19.09985-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of body fat in male athletes from ultrasound and anthropometric measurements versus DXA

Abstract: Prediction of body fat in male athletes from ultrasound and anthropometric measurements versus DXA. Abstract Background: To compare the accuracy of body fat percentage (BF%) measured by an ultrasound portable device and anthropometric measurements with a Dual Energy X-ray Absorptiometry (DXA) as the reference technique in male athletes. Methods: A total of 100 athletes: 16 boxers, 4 rowers, 5 gymnasts, 6 base ball players, 19 judo players, 10 taekwondo players, 7 basket-ball players, 21 wrestlers, 6 cyclists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although we have used a relatively larger number of participants, we presume that we would find more robust effect sizes and statistical power if we recruited more participants. Furthermore, we estimated body fat percentage by using the skinfold thickness method, which is certainly less accurate than a more direct assessment utilizing a dual-energy X-ray absorptiometry (DEXA) or magnetic resonance imaging (MRI) scan 42 . Finally, the current study involved only men and not women.…”
Section: Discussionmentioning
confidence: 99%
“…Although we have used a relatively larger number of participants, we presume that we would find more robust effect sizes and statistical power if we recruited more participants. Furthermore, we estimated body fat percentage by using the skinfold thickness method, which is certainly less accurate than a more direct assessment utilizing a dual-energy X-ray absorptiometry (DEXA) or magnetic resonance imaging (MRI) scan 42 . Finally, the current study involved only men and not women.…”
Section: Discussionmentioning
confidence: 99%
“…US can be used in a wide variety of people ranging from extremely lean to obese, [24] and has been applied in various groups, including basketball players. [22,[25][26][27][28][29] However, to the best of our knowledge, no study has simultaneously reported the US normative values for GM and RF (muscle thickness [MT] and SFT), comparing these results between different age-categories and genders in young elite basketball players. Considering all the above, the aims of the present study were to (1) obtain normative data from physical tests [CMJ and V-cut] and ultrasound measurements [MT and the adjacent SFT of the GM and RF] of different age-category male and female elite youth basketball players; (2) evaluate possible between-agecategory (U14, U16, and U18) and between-gender (male or female) differences in all these data; and (3) examine the relationships between physical and US measurements and determine the combination of variables that most accurately predict the abilities of jumping and sprinting with COD in males and females.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In addition, US is particularly useful for field settings because of its portability. US can be used in a wide variety of people ranging from extremely lean to obese [24], and has been applied in various groups, including basketball players [22,[25][26][27][28][29]. However, to the best of our knowledge, no study has simultaneously reported the US normative values for GM and RF (muscle thickness [MT] and SFT), comparing these results between different age-categories and genders in young elite basketball players.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods use readily available devices such as calipers to measure dimensions (Agyapong Afrifah & Glalah, 2021; Hajaghazadeh et al, 2018), but modern methods digitally model the human body utilizing stereophotogrammetry, computed tomography (CT), magnetic resonance imaging (MRI), and 3D scanning methods (Fu & Luximon, 2020; Li et al, 2008). Researchers apply these methods to collect data in variety of field, including military (da Silva et al, 2018), nutrition (Kamruzzaman et al, 2021), medicine (Utkualp & Ercan, 2015), sport (Pineau & Bouslah, 2019), and design (da Silva et al, 2020). Practitioners in the field of ergonomics or human factor collect and present data to designers to maximize the fit between humans and products, which can lead to easier work, increased safety, fewer body injuries, and higher job satisfaction (Dianat et al, 2018).…”
Section: Introductionmentioning
confidence: 99%